Community based research partnerships for co-constructing participatory forms of social justice research and action - Schensul, Jean Jessica (Tracce urbane. Rivista italiana transdisciplinare di studi urbani, 2020)
Questo contributo esamina due forme di co-costruzione di conoscenza e azione che hanno entrambe un impatto su questioni di giustizia sociale in contesti comunitari, la Participatory Action Research e la Community Based Participatory Research. Definisce la CBPR come alleanze tra organizzazioni comunitarie e partner universitari per il cambiamento; e la PAR come ricerca guidata dalla comunità per la costruzione di alleanze e per l’advocacy. Il documento descrive alcuni esempi di entrambe, illustrati attraverso il lavoro dell’Institute for Community Research, un’organizzazione di ricerca indipendente basata sulla comunità. Suggerisce argomenti sul motivo per cui gli antropologi dovrebbero considerare la formazione di organizzazioni di ricerca basate sulla comunità e i loro vantaggi nel condurre CBPR e PAR per affrontare le questioni di giustizia sociale. Rileva inoltre i vantaggi della collaborazione tra tali organizzazioni e le università per estendere la portata delle università e le risorse per la risoluzione dei problemi delle comunità. Il documento sostiene un maggiore coinvolgimento degli antropologi sia nella CBPR che nella PAR. This paper examines two forms of co-constructing knowledge and action both impacting on social justice issues in community settings, Participatory Action Research and Community Based Participatory Research. It defines CBPR as alliances between community organizations and university partners for change; and PAR as community-led research for alliance building and advocacy. The paper describes examples of both illustrated through work of the Institute for Community Research, an independent community based research organization. It suggests arguments for why anthropologists should consider the formation of community based research organizations and their advantages for conducting CBPR and PAR to address social justice issues. It also notes the advantages of university collaboration with such organizations to extend university reach and community problem solving resources. The paper endorses greater involvement of anthropologists in both CBPR and PAR.